If y2 + 13y = 40, then y ~ 15.55If y2 + 13y = 0, then y = -13Improved Answer:-y2+13y+40 = 0(y+5)(y+8) = 0Therefore: y = -5 and y = -8
88 + 5y - y2 66 - 3y + y2 Subtract: 22 + 8y -2y2
Do you mean: y2+13y+40 = 0 If so then when factored: (y+5)(y+8) = 0 Therefore: y = -5 and y = -8.
y2 + y2 = 2y2
a2+b2+c2=x2+y2+z2 divide each side by 2 (a2+b2+c2)/2=(x2+y2+z2)/2 a+b+c=x+y+z
There is no expansion for x2 + y2
4 - y2 can be written as 22 - y2. This has become of the form of x2 - y2.Expansion for x2 - y2 is (x+y)(x-y).So, 4 - y2 = 22 - y2 = (2+y)(2-y)
All you can do to factor that expression is to divide both terms by y: y2 + 4y = y(y + 4)
x2 + 2x + y2 = 12 (complete the square)(x2 + 2x + 1)+ y2 = 12 + 1(x + 1)2 + y2 = 13 (divide by 13 each element to both sides)(x + 1)2/13 + y2/13 = 1(x - -1)2/13 + (y - 0)2/13 = 1Thus, the center of the circle is (-1, 0) and its radius is 1.
y4Improved Answer:-y2+y2 = 2y2
This is not factor-able.
x2 + y2 = 2r2
25x2 - 10xy + y2 = (5x - y)2
(y - 5)(y - 6)
( -12 x8 y8 ) / ( 3 x4 y2 ) = -4 x4 y6
yes that is correct
4a2 + 4ab - y2 + b2 You cannot simplify this expression because it does not contain like terms, but you can factor it such as: 4a2 + 4ab - y2 + b2 = (4a2 + 4ab + b2) - y2 = (2a + b)2 - y2 = [(2a + b) - y][(2a + b) + y]
4x-y2=2xy 2x ? y5 if its plus its 7 xy
X2 + y2 = 100 = r2 r = 10